Impact of preoperative dental anxiety on intraoperative pain perception during tooth extraction: a cross-sectional study - Saeed, Tooba; Ahmad Liaquat; Ammar Niazi; Ijaz Ur Rehman; Salman Amin; Tahmasub Faraz Tayyab (Journal of University Medical & Dental College, 2024)
ABSTRACT: BACKGROUND AND OBJECTIVE: Dental anxiety is a global concern. Due to this, patients may experience the same dental procedures differently. According to the literature, tooth extraction is a dental procedure that provokes a high level of dental anxiety. This study aims to explore the relationship between preoperative dental anxiety and intraoperative pain perception during tooth extraction. Identifying various factors that trigger dental anxiety is important for understanding psychological influences on dental experiences. METHODOLOGY: This cross-sectional study was conducted at the University Dental Hospital, The University of Lahore. After obtaining ethical approval, 195 participants were included. Corah’s Dental Anxiety Scale and the Visual Analog Scale were used to measure anxiety level and pain perception. Statistical analyses, including one-way ANOVA and correlation tests, were performed using SPSS software (version 25.0) to evaluate the relationships between preoperative anxiety, intraoperative pain, and various influencing variables. RESULTS: Findings showed a significant positive correlation between preoperative anxiety and intraoperative pain perception. Females exhibited higher anxiety levels than males. Patients with a history of previous extractions or those undergoing molar extractions had increased anxiety. Interestingly, patients with high to severe anxiety reported experiencing less pain, possibly due to the expertise of the treating surgeons. CONCLUSION: The study highlights the intricate relationship between preoperative dental anxiety and intraoperative pain during tooth extraction. Insights obtained can help develop personalized care strategies, contributing to a broader understanding of psychological aspects in dental settings. Further research with varied populations is recommended to validate the study’s findings.